SMALL AND MEDIUM SCALE BUSINESS MANAGERS’ RATINGS OF OPERATIONAL COMMUNICATION STRATEGIES FOR SUCCESS OF ENTERPRISES IN ENUGU STATE (NAU Journal of Technology and Vocational Education, 2024)
The need for SMEs to thrive in the Nigerian economy necessitated the study todetermine small and medium scale business managers’ ratings of operationalcommunication strategies for success of enterprises in Enugu State. One researchquestion guided the study and two null hypotheses were tested at 0.05 level ofsignificance. The design of the study was a descriptive survey. Population of the studywas all the managers of the 911 registered SMEs in Enugu State. A sample of 220managers was selected using proportionate stratified random sampling technique.This comprised 196 managers of small and 24 managers of medium enterprises.Instrument for data collection was a structured questionnaire titled “Managers’Ratings of Operational Strategies for Success of Enterprises Questionnaire(MROSSEQ)” validated by three experts. A reliability coefficient of 0.84 wasestablished using test-retest method and Pearson Product Moment CorrelationCoefficient to obtain the value. Mean and standard deviation were used to analyzedata relating to the research question while z-test was used to test the null hypotheses.Findings revealed that all the operational communication strategies were highlyrelevant to the success of SMEs in Enugu State. Also, gender and years of experiencedid not influence the opinions of the SME managers regarding the relevance ofoperational communication strategies for success of their enterprises. Consequently,it was recommended among others that SMEs business managers in Enugu Stateshould make concerted efforts to adopt the operational communication strategiesidentified in this study and also engage themselves in the training that will educatethem more on operational communication strategies in order to keep their businessesviable.
Keywords: operational communication strategy, Small and medium enterprise (SME), success.